Affiliative nomads in Japan: potential sustainable tourism stakeholders in depopulated rural areas - Horiuchi, Shiro; Morishige, Masayuki (Frontiers in Sustainable Tourism, 2024)
In Japan, the overall population is declining. Depopulation is severe, resulting in various negative consequences, particularly in rural areas. Rural communities could benefit by collaborating with people from other places, mainly urban areas. Typical examples of visitors or tourists from urban areas in these cases are referred to as “kankei jinko.” The more fundamental issue, however, is that many rural residents have lost confidence in their ability to live in areas with declining and aging populations. It is important to note the potential for highly mobile people from urban areas to increase the civic pride of rural residents. This raises questions about who these nomadic people, or “affiliative nomads,” are and how they interact with residents. To answer these questions, we analyzed cases of affiliative nomads in previous studies. The nomadic people showed respect for the rural areas to the residents; as a result, they were perceived by the residents as being in a stage of growth. When the nomads and residents interact, they create common values such as nature conservation and economic and community revitalization. Thus, the nomads cultivate civic pride among the residents and could be regarded as affiliative nomads. Furthermore, some coordinators bridge residents and nomads to expand their relationships with other people. Affiliative nomads may be sustainable tourism stakeholders and contribute to solving the problems of depopulated areas in Japan and other developed or emerging countries.